2014
DOI: 10.1111/cdoe.12127
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ decisions to conduct caries risk assessment in a Dental Practice‐Based Research Network

Abstract: Objectives 1) To quantify the importance that dentists place on caries risk factors when developing a caries treatment plan, and 2) to test the hypothesis that the ratings of importance for specific factors are significantly associated with whether or not the dentist performs caries risk assessment (CRA). Methods This study used a cross-sectional study design consisting of a questionnaire survey. The study queried dentists who worked in outpatient dental practices who were affiliated with the Dental Practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
2
22
1
1
Order By: Relevance
“…Questionnaires were distributed to 282 dentists, from whom valid responses were obtained from 189 (67 percent). Demographic characteristics of participants are provided in Table 1 (7,(15)(16)(17)(18). Mean number of years (±standard deviation) since graduation from dental school was 18.5 ± 9.9.…”
Section: Demographic Information Of Participantsmentioning
confidence: 99%
“…Questionnaires were distributed to 282 dentists, from whom valid responses were obtained from 189 (67 percent). Demographic characteristics of participants are provided in Table 1 (7,(15)(16)(17)(18). Mean number of years (±standard deviation) since graduation from dental school was 18.5 ± 9.9.…”
Section: Demographic Information Of Participantsmentioning
confidence: 99%
“…Some discussion has already been initiated among some countries and ongoing work anticipates a fruitful collaboration. 56-60 …”
Section: Paradigm Shiftmentioning
confidence: 99%
“…Participants were dentists who worked in an outpatient dental practice and were affiliated with the JDPBRN (n = 282) [14][15][16][17][18][19] . They were recruited using the JDPBRN website, as well as by a targeted mailing to members who had indicated that they perform restorative dentistry in their practices.…”
Section: Participantsmentioning
confidence: 99%
“…The recent establishment of the Dental Practicebased Research Network Japan (JDPBRN) (http:// www.dentalpbrn.jp/) created an opportunity for international comparisons. The JDPBRN has identified that an evidence-practice gap exists in caries treatment 14,15 , caries risk assessment 16 , dietary counselling 17 and caries prevention 18,19 . However, actual dentist practice patterns regarding sealant provision, and how these patterns vary with caries severity, remain unclear.…”
Section: Introductionmentioning
confidence: 99%